2022
DOI: 10.1111/jipb.13347
|View full text |Cite
|
Sign up to set email alerts
|

The SlTPL3–SlWUS module regulates multi‐locule formation in tomato by modulating auxin and gibberellin levels in the shoot apical meristem

Abstract: Malformed fruits depreciate a plant's market value. In tomato (Solanum lycopersicum), fruit malformation is associated with the multi‐locule trait, which involves genes regulating shoot apical meristem (SAM) development. The expression pattern of TOPLESS3 (SlTPL3) throughout SAM development prompted us to investigate its functional significance via RNA interference (RNAi) and clustered regularly interspaced short palindromic repeats/CRISPR‐associated nuclease 9 (Cas9)‐mediated gene editing. Lower SlTPL3 transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Alternatively, the homeostasis of GA and ABA in the OC region of FM may also be directly regulated by SlWUS. Previously, it was reported that both SlGA3ox (Solyc03g119910), involved in GA biosynthesis, and SlGA2ox4 (Solyc07g061730), involved in GA metabolism, exhibited upregulation in RNAi‐SlTPL3 tomato lines (Song et al ., 2022). As SlTPL3 acts as the inhibitor of SlWUS in the late stage of floral development (Bollier et al ., 2018), it is reasonable to infer that SlWUS could influence GA biosynthesis or metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the homeostasis of GA and ABA in the OC region of FM may also be directly regulated by SlWUS. Previously, it was reported that both SlGA3ox (Solyc03g119910), involved in GA biosynthesis, and SlGA2ox4 (Solyc07g061730), involved in GA metabolism, exhibited upregulation in RNAi‐SlTPL3 tomato lines (Song et al ., 2022). As SlTPL3 acts as the inhibitor of SlWUS in the late stage of floral development (Bollier et al ., 2018), it is reasonable to infer that SlWUS could influence GA biosynthesis or metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the formation of multiple locules in tomato fruits is achieved by modulating the levels of auxin and gibberellin (GA) in apical meristems, for which the transcriptional repressor TPL3 and WUS are responsible [128]. A protein interaction was found between them, ensuring the regulation of auxin transporter genes and enzymes for gibberellin biosynthesis.…”
Section: Ovary Development and Fruit Sizementioning
confidence: 99%